The prevalence of sarcopenia in middle‐aged and older patients in post‐acute inpatient rehabilitation: a cross‐sectional study - Irina Churilov; Leonid Churilov; Kim Brock; Navina Curtain; David Murphy; Kavitha Muthukrishnan; Richard J. MacIsaac; Elif I. Ekinci (Wiley, 2021)
Abstract Background Despite the recommendation of European Working Group on Sarcopenia in Older People 2 (EWGSOP2) consensus statement not to exclude patients younger than 65 years, the prevalence of sarcopenia has not been investigated in younger post‐acute inpatient rehabilitation population. The objectives of this study were to: i) estimate the prevalence of sarcopenia in post‐acute inpatient rehabilitation population; ii) compare the prevalence of sarcopenia in patients above and below 65 years. Methods This cross‐sectional observational study recruited adult patients admitted to an inpatient rehabilitation unit at a metropolitan tertiary referral hospital in Melbourne, Australia. Participants' sarcopenia status was determined using the EWGSOP2 algorithm based on grip strength and muscle mass. Results Between November 2016 and January 2019, 203 participants were enrolled. Participants' broad diagnostic streams included musculoskeletal, neurologic, spinal, cardiac, amputee, and deconditioning. The overall prevalence of sarcopenia was 18% [95% confidence interval (CI) 13% to 24%]. The prevalence of sarcopenia in patients younger than 65 was 14% (95% CI 8% to 22%), and the prevalence in patients 65 and older was 23% (95% CI 15% to 32%), risk difference of 9% (95% CI: −1.2% to 20%; P = 0.1). With incorporation of these results into the most recent meta‐analysis of sarcopenia in inpatient rehabilitation, the mean pooled prevalence of sarcopenia was 47% (95% CI 23% to 71%). Stratified by age, patients with sarcopenia had significantly longer preceding length of stay in the acute hospital (P = 0.015). Conclusions The overall estimated prevalence of sarcopenia in patients admitted to inpatient rehabilitation was 18%, and the estimated prevalence of sarcopenia in patients younger than 65 was 14%.